1995
DOI: 10.1002/stem.5530130310
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic administration of granulocyte colony‐stimulating factor (filgrastim) after conventional chemotherapy in children with cancer

Abstract: We evaluated granulocyte colony-stimulating factor (G-CSF) as an adjunct to courses of conventional chemotherapy in 16 children with cancer. One course followed by G-CSF (20 episodes) was compared to identical courses without G-CSF (20 episodes) in the same patients. The mean duration of G-CSF therapy was 8.8 (5-13) days. The periods of neutropenia (4.8 days versus 16.5 days; p < 0.0001), days of hospitalization for febrile neutropenia (13 days versus 65 days; p = 0.02) and days on broad-spectrum antibiotics (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
5

Year Published

1999
1999
2003
2003

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 22 publications
1
24
0
5
Order By: Relevance
“…The reported effects of G-CSF or GM-CSF on chemotherapy-induced thrombocytopenia have been inconsistent. 7,15,[22][23][24][25][26] To our knowledge, no study before ours has examined the issue regarding G-CSF in patients with solid tumors beyond one to three cycles of chemotherapy. The comparable platelet transfusion requirements of our two groups 1) reflect the immediate thrombocytopenic potency of the chemotherapy, regardless of G-CSF usage, and 2) indicate a problem with delay in full recovery of platelet counts rather than with the depth of nadir counts.…”
Section: Discussionmentioning
confidence: 99%
“…The reported effects of G-CSF or GM-CSF on chemotherapy-induced thrombocytopenia have been inconsistent. 7,15,[22][23][24][25][26] To our knowledge, no study before ours has examined the issue regarding G-CSF in patients with solid tumors beyond one to three cycles of chemotherapy. The comparable platelet transfusion requirements of our two groups 1) reflect the immediate thrombocytopenic potency of the chemotherapy, regardless of G-CSF usage, and 2) indicate a problem with delay in full recovery of platelet counts rather than with the depth of nadir counts.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, one other report in the literature found a cost savings for G-CSF use in the pediatric setting. Riikonen et al demonstrated a $1,033 savings per chemotherapy cycle for 16 pediatric cancer patients (mainly hematologic malignancies) receiving G-CSF as treatment for febrile neutropenia [6,7]. Clearly the use of growth factors, though seeming to provide some clinical benefit, for pediatric leukemia requires further investigation and optimization.…”
Section: Discussionmentioning
confidence: 95%
“…However, this treatment can be highly toxic, causing severe and prolonged neutropenia and delays in therapy and/or repeated hospitalizations. Studies have been published investigating the use of colony-stimulating factors (CSFs) as prophylactic or adjunct therapy for chemotherapyinduced neutropenia in pediatric patients [5][6][7]. The aim of this treatment is to reduce the length of time and severity of neutropenia and the risk of infection.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our previous study we evaluated the use of G-CSF as an adjunct to courses of conventional chemotherapy in children with cancer [6]. We found that the use of G-CSF (+1 day postchemotherapy) facilitated myeloid recovery significantly and reduced the number of infectious complications and hospital days due to febrile neutropenia.…”
Section: Discussionmentioning
confidence: 97%